Prevalence of Digestive Endoparasites (Helminth and Protozoa) in Domestic Pigeon (Columba livia) Male and Female in Tuban - Melanie Aulia Ashfiyah; Setiawan Koesdarto; Hana Eliyani; Mufasirin Mufasirin; Emy Koestanti Sabdoningrum (Journal of Parasite Science (JoPS), 2022)
This research was conducted to determine the prevalence of major gastrointestinal helminthiasis and protozoal infections, the kinds of helminth and protozoa that infects and the effect of sex on pigeons in Tuban. Pigeons are taken from five The Tuban area is Widang, Montong, Jenu, Soko, Jatirogo. Each area is taken as many as 20 pigeons consists of 10 male pigeons and 10 female pigeons. Laboratory examinations were carried out in November to December 2021. Samples were examined by the native method, sedimentation, and flotation. Identification using a microscope using a 40x objective scale and 10x ocular scale. Data analysis using chi square test statistical analysis. 81% of the samples were positive for helminthiasis infection. Chi square test statistical analysis showed p value 0.022 (p<0.05) which means significantly different. 71% of samples were positive for gastrointestinal protozoa infection in pigeons in Tuban. Chi square test Results Statistical analysis shows p the value of 0.123 (p>0.05) which means that it is not significantly different. Type of protozoa found that Heterakis gallinarum (45%), Ascaridia columbae (42%), Capillaria sp. (41%), and Eimeria sp. (71%). That prevalence of helminthiasis in male pigeons higher (45%) compared to female pigeons (36%).